Integrasi Pembelajaran PAI dengan Budaya Sekolah Peduli Lingkungan dalam Membangun Kepedulian Lingkungan di Sekolah Alam Islam Aisyah Radhiyallahu’Anha - Nabila, Farisatun; Efferi, Adri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the concept, strategy, and effectiveness of integrating Islamic Religious Education (PAI) learning with an environmentally conscious school culture in building students' ecological awareness at Aisyah Islamic Nature School (Sekolah Alam Islam Aisyah Radhiyallahu'Anha). This study is motivated by the urgency of strengthening religious character while caring for the environment in Islamic educational institutions. The method used is a qualitative approach with a case study. Data were collected through direct observation and semi-structured interviews with PAI teachers and 5th grade students. The results of the study indicate that the integration of Islamic religious education values ​​​​with environmental concern is implemented through a thematic curriculum, habituation, and collaboration between educators and school residents. Students not only understand Islamic values ​​​​conceptually, but are also able to internalize and practice them in everyday life. The findings of this study indicate that the integration model is effective in building religious character while caring for the environment. This study contributes in the form of a character education model based on religious and environmental values ​​​​that can be adapted by other Islamic schools.